BLOOD MARRIAGE AND CHILD STATUS IN INHERITANCE PERSPECTIVE OF IMAM NAWAWI - Abdul Hakim (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
Islam is a religion that upholds the rights and obligations of all human beings and cares for all the aspects needed in life. Some of the most important aspects of life that must be fulfilled are the distribution of libido properly and in accordance with the provisions of applicable norms. This is where Islam nenata and strictly regulates the concept of marriage. As for the ins and outs of marriage, especially regarding the boundaries of blood marriage or close relatives, the researcher specializes in the conception of Imam Nawawi's perspective as the main reference for research, especially in the context of the consequences of the marriage law and what is the status of the inheritance rights of the children resulting from the marriage. Some general findings regarding this research, the majority of the Ashabul Mazdhab found that as long as there was no intentional element, the marriage was classified as wath' syubhat and the child resulting from the marriage was a tabi' child, namely obtaining full inheritance rights from both parents. Based on Imam Nawawi's perspective, the consequences of inbreeding marriage are grouped into several points: if there is an intentional marriage the two are fasid and both are punished with death and their property is confiscated as is the law of the origin of adultery against a mahrom, if it is based on mutual ignorance both of them are punished with wath' syubhat, but if one of them Among them there are those who hide the truth, so for them they are killed and their property is confiscated, while the status of children's inheritance rights follows the marital status of their parents.